The dust bowl - Farris, John, 1940-; Manning, Maurie (San Diego : Lucent Books, 1989)
Discusses the disastrous drought in the United States during the 1930s which made a "dust bowl" out of a part of the Great Plains, causing great hardship to farmers.
Includes bibliographical references (p. 60) and index.
Keywords: Droughts -- Southwestern States -- History -- 20th century -- Juvenile literature; Droughts -- Great Plains -- History -- 20th century -- Juvenile literature; Depressions -- 1929- -- Southwestern States -- Juvenile literature; Depressions -- 1929- -- Great Plains -- Juvenile literature; Agriculture -- Southwestern States -- History -- 20th century -- Juvenile literature; Agriculture -- Great Plains -- History -- 20th century -- Juvenile literature; Dust Bowl Era, 1931-1939 -- Juvenile literature; Droughts -- Great Plains -- History; Agriculture -- Great Plains -- History; Dust storms -- Great Plains; Southwestern States -- History -- Juvenile literature; Great Plains -- History -- Juvenile literature; Great Plains -- History